Strategic Planning of National Development: International and Ukrainian Experience. Part I. International Experience of Strategic Planning - Sitnikova, N. P.; Kulak, А. O. (Statistics of Ukraine, 2024)
The article examines the strategic planning of national and sustainable development, focusing on international experiences in the first part and the state of national strategic planning in the second part. It discusses the legislative framework for strategic planning and the development of long-term strategies for national and sustainable development. The first part provides an overview of strategic planning frameworks in the United States, the United Kingdom, Canada, and the EU, as well as international experiences in formulating national and sustainable development strategies within the EU. This section emphasizes the strategic planning process and the establishment of monitoring indicators for evaluating interventions, strategies, and programs. EU countries adopt a participatory approach to goal-setting, integrate digital technologies into monitoring processes, and define standards for evaluation of strategic documents. Planning processes in the EU are rooted in results-based management principles, particularly the theory of change, and evidence-based decision making. Goal-setting is informed by research on national development specifics, the participatory identification of social needs, and a long-term vision for the country’s future. The targets of national and sustainable development strategies, along with their corresponding indicators, are clearly aligned with the overall goals. These strategies guide other medium-term plans, programs, and budget processes for the medium term. The direction and pace of future transformations in each country largely depend on setting targets, programming, and establishing a system of action plans and measures with defined indicators, as well as on the evaluation of previous development strategies. Most strategies in developed countries incorporate a digital monitoring model. Analyzing the dynamics of indicators set as targets in the strategic documents of developed countries, along with reviewing reports and their public presentation, reveals that open public monitoring of government institutions’ commitments to the national development strategy is a hallmark of democratic society.